Pembelajaran Bilingual: Pemerolehan dan Perkembangan Bahasa Kedua Terhadap Kemampuan Kognitif Anak Bilingual - Muhammad Hanif Hukama; Damara, Irey; Fauzi Rachman, Ichsan (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
This research focuses on the implementation of bilingual learning in schools from early childhood which can influence the acquisition and development of a second language and children's cognitive abilities. The aim of this research is to describe theories from the results of several other studies regarding the influence of second language acquisition on the cognitive abilities of bilingual children. The research method used is qualitative with a library study approach to collect information from various library sources that are relevant to the research topic. The data sources in this research were obtained from books and articles that discuss the phenomenon of bilingualism as well as research results that refer to the cognitive abilities of bilingual children. In the results and discussion section, it can be concluded that children's acquisition of a second language can influence cognitive abilities. Bilingual learning makes students more flexible in multilingual environments and provides better opportunities to participate in global society. From a cognitive perspective, bilingual children have better skills than monolingual children. However, the effectiveness of bilingual learning can be achieved if it is facilitated by several supporting factors. Overall, the advantages of bilingual children outweigh the disadvantages